Ruptured Liver Abscess Post Severe COVID-19 Infection: A Case Report - Isa, Mohd Firdaus Mohd; Ghazi, Faiz Najmuddin; Merican, Siti Rahmah Hashim Isa; Zulkifli, Ahmad Zuraimi; Singh, Premjeet (Prague medical report, 2024)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) caused imminent acute infection of respiratory tract known as Coronavirus disease 2019 (COVID-19). Complications of hepatobiliary system especially liver often found in post-acute COVID-19 patients. However, there are only few studies specifically discussing about liver abscess in patients who had history of contracted COVID-19. We present a case of a 54-years-old gentleman with no previous medical illness and no history of vaccination, who was presented with ruptured liver abscess post COVID-19 infection Category 4 (symptomatic with lung infection and the need of oxygen supplementation). Percutaneous drainage was performed to drain the abscess and collections.
Keywords: lidé středního věku; Drainage; lidé; Rupture, Spontaneous; mužské pohlaví; SARS-CoV-2; spontánní ruptura; Male; absces jater; Middle Aged; drenáž; COVID-19; Liver Abscess; Humans